Exploring Students' Attitudes Toward Learning Writing: A Case Study at English Education Department of an Islamic University - Rahna Husnaini; Bukhori, Bukhori (IJET (Indonesian Journal of English Teaching), 2024)
Writing Attitudes refers to the perceptions, feelings, and beliefs that students hold towards writing. Understanding students' writing attitudes is important as it can affect their engagement in writing activities and ultimately their writing performance. The aims of this study are to describe the attitudes towards learning writing and to identify the contributing factors the attitudes towards learning writing of EFL students in the English Education Department of an Islamic university in Pekanbaru. This research is qualitative research. This research was conducted from January to February 2024 at an Islamic university in Pekanbaru, Indonesia. The participants were 6 students of 3rd semester students. To this extent, it was generally studied that the sampling size for this study purposively comprises one class with 30 students in total from the English Education Department, which serves as a representative group. The instruments to collect the data were close-ended questionnaire, open-ended questionnaire, and interview. The researcher used qualitative analysis: data reduction, data display, and conclusion drawing/verification to analyse the data. The result shows that there are three attitudes that were shown by the 3rd semester students at English Education Department of an Islamic University in Pekanbaru namely beliefs, emotions, and dispositions. in addition, the factors that influenced the students’ attitude were teaching method and approaches, curriculum and materials, leacturer interactions, and peer influence and collaboration factors.